Applicability of the Spanish Translation of the Zung Self-Rating Depression Scale in a General Puerto RIcan Population - Martínez, Karen G.; Guiot, Humberto M.; Casas-Dolz, Ingrid; González-Tejera, Gloria; Colón De Martí, Luz N. (Puerto Rico Health Sciences Journal, 2011)
see manuscript